Graphene-Modified Electrodeposited Dendritic Porous Tin Structures as Binder Free Anode for High Performance Lithium-Sulfur Batteries. (20th November 2016) - Hari Mohan, E.; Sarada, B.V.; Venkata Ram Naidu, R.; Salian, Girish; Haridas, Anulekha K.; Appa Rao, B.V.; Rao, Tata N.
Graphical abstract: Highlights: Use of carbon paper as substrate for both anode and cathode materials. Electrodeposition and Co-electrodeposition of pristine Sn and Sn/G composite. Formation of sandwich type architecture of 3D porous pristine Sn and Sn/G composite. An improved electrochemical performance of Sn/G/RGO anode and sulfur/carbon cathode. Demonstration of a simple and low cost Li-S battery in full-cell configuration Abstract: In this paper, we report a novel Sn/G/RGO-S battery with high capacity and good cycle life in comparison to conventional lithium-ion batteries. Low cost electroplating and drop cast method are developed for the first time to prepare binder free highly porous 3D Sn/G/RGO composite on carbon paper substrate as anode. The unique 3D porous network of Sn/G composite allows better accommodation of volume expansion induced by Li insertion, while presence of graphene in the co-electrodeposited Sn/G composite provides enhanced electron conduction. Additional coating of RGO on the surface of co-electrodeposited Sn/G composite protects the electrode surface from the direct electrolyte contact, and minimizes the progressive SEI formation during repeated charge-discharge cycles. Consequently, Sn/G/RGO electrode in half-cell exhibits a much superior electrochemical performance and better cycle life. We also demonstrate a full-cell by using S/C as cathode and Sn/G/RGO composite with a very thin lithium foil on the surface as anode in order to avoid serious safety issues allied with lithium metal. Sn/G/RGO-S full cell delivers a high discharge capacity of 413 mAh g −1 at the end of 40 cycles. The cell delivers a specific energy of about 660 Wh kg −1 based on the weight of sulfur and 336 wh kg −1 based on the total mass of the S/C electrode. The simple designed and cost effective technique to fabricate high performance Sn/G/RGO-S battery would be feasible for alternative clean energy sources.